The Effect of Swaddling, Stomach Position, Shushing, Swinging, Sucking Methods on Pain Responses of Infants After Basic Immunization in the Dahlia Health Center Area - Nahira Nahira; Sumarni Sumarni; Wa Ode Sitti Fidia Husuni (International Journal of Health and Social Behavior, 2024)
Immunization via injection can cause immediate pain in children. Pain that occurs as a result of immunization injections, if not managed properly, can have a negative impact on the child's emotional aspects such as crying and fear. This research uses a quasi-experimental method with a one group pretest-posttest design approach. The sample involved in this research was 64 respondents, selected using Probability Sampling techniques. The research results show that based on the Paired T-Test statistical test, the p-Value value for the influence of the 5S Method (Swaddling, Side-Stomach, Shushing, Swinging, Sucking) is 0.000. Because p < 0.05, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (H0) is rejected. Thus, it can be concluded that the 5S Method (Swaddling, Side-Stomach, Shushing, Swinging, Sucking) has a significant influence on the Infant's Pain Response After Basic Immunization at the Dahlia Makassar Community Health Center. The suggestion is that the 5s method be an alternative for treating pain experienced by babies as an effort to minimize pharmacological therapy.